Noninferiority of cetuximab every-2-weeks versus standard once-weekly administration schedule for the first-line treatment of RAS wild-type metastatic colorectal cancer. (February 2021) - Kasper, Stefan; Foch, Caroline; Messinger, Diethelm; Esser, Regina; Lamy, Francois-Xavier; Rothe, Vivien; Chen, Wenfeng; Cheng, Ann-Lii; Rouyer, Magali; Brodowicz, Thomas; Zielinski, Christoph
Abstract: Aim: This study assessed whether cetuximab 500 mg/m 2 administered every 2 weeks (Q2W), when combined with chemotherapy as a first-line (1L) treatment, was noninferior to the approved dose (400 mg/m 2 followed by 250 mg/m 2 once weekly [Q1W]) for overall survival (OS) in adults with RAS wild-type metastatic colorectal cancer (mCRC). Methods: This pooled analysis included patients receiving 1L treatment with cetuximab Q1W or Q2W in combination with chemotherapy from post-authorisation studies with patient-level data available to the sponsor. Baseline characteristics were adjusted with a propensity score using inverse probability of treatment weighting (IPTW). Noninferiority in terms of OS was tested with a noninferiority margin for the hazard ratio (HR) of 1.25 using a Cox proportional hazards regression model. Secondary outcomes were progression-free survival (PFS), overall response rate (ORR) and rates of lung/liver metastases resection and serious adverse events. Results: OS time was noninferior in the Q2W cohort (n = 554) compared to the Q1W cohort (n = 763), with a HR after IPTW (95% confidence interval) of 0.827 (0.715–0.956) and median OS times of 24.7 (Q1W) and 27.9 (Q2W) months. There were no major differences in PFS (HR: 0.915 [0.804–1.042]). The odds ratios (ORs) after IPTW for ORR (1.292 [1.031–1.617]) and the rates of lung/liver metastases resection (1.419 [1.043–1.932]) favoured the Q2W regimen. No differences were noted in the occurrence rate of any SAE between groups; the OR after IPTW was 1.089 (0.858–1.382). Conclusions: The cetuximab Q2W regimen was noninferior to the Q1W regimen for OS in the 1L treatment of mCRC. Highlights: A pooled analysis of patients given 1L cetuximab Q1W or Q2W was performed. Results showed noninferiority of Q2W dosing for OS. PFS and safety were unaffected by dosing. Resection rates of lung/liver metastases favoured Q2W schedule.